2022
DOI: 10.1007/s00289-022-04445-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in industrial and academic developments of green tyre technology

Abstract: Growing natural calamities as a consequence of global warming are one of the most pondering subjects today. The exponential growth of environmental pollution due to unscientific human exploitation of natural resources is considered the prime reason for the harsh responses of nature. Researchers from various fields of industry and academia are working hard to develop and implement products/technologies that are environmentally friendly or less harmful to the ecosystem. Material researchers, specifically those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…Among the components, synthetic polymers, rubber process oils, and carbon blacks are nonrenewable and petroleum resourced. Out of the automobile industry’s share of 40% global pollution, tire contributes to a hefty 20–30%. , Tire manufacturing also contributes to carbon dioxide emissions and the depletion of petrochemical resources . Several studies also show an ubiquitous presence of the much-discussed tire and road wear particles (TRWP) in the air, water, and soil. TRWP quantification studies show that 1 000 000 ton/yr of TRWP has been reported in the U.S. alone. , Further, several degradation studies of tire particles show that tire leachate from the additives can be present in the environment after prolonged exposure. Moreover, TRWP is shown to have environmental implications like human health risk on the liver and kidneys and respiratory irritation, and acute toxicity on aquatic life such as the coho-salmon species. Thus, there is a primal need for sustainable formulation by incorporating more environmentally friendly materials.…”
Section: Introductionmentioning
confidence: 99%
“…Among the components, synthetic polymers, rubber process oils, and carbon blacks are nonrenewable and petroleum resourced. Out of the automobile industry’s share of 40% global pollution, tire contributes to a hefty 20–30%. , Tire manufacturing also contributes to carbon dioxide emissions and the depletion of petrochemical resources . Several studies also show an ubiquitous presence of the much-discussed tire and road wear particles (TRWP) in the air, water, and soil. TRWP quantification studies show that 1 000 000 ton/yr of TRWP has been reported in the U.S. alone. , Further, several degradation studies of tire particles show that tire leachate from the additives can be present in the environment after prolonged exposure. Moreover, TRWP is shown to have environmental implications like human health risk on the liver and kidneys and respiratory irritation, and acute toxicity on aquatic life such as the coho-salmon species. Thus, there is a primal need for sustainable formulation by incorporating more environmentally friendly materials.…”
Section: Introductionmentioning
confidence: 99%
“…Production and consumption of tyres have a major role in environmental pollution and it has a direct impact on global warming. Around 82% of such hazards arise from tyre usage and processing, which eventually contributes to around 20% of total environmental hazardousness 2 . Recycling, reusing, and utilization of less hazardous/renewable resource‐based raw materials are the possible methods suggested by the experts to overcome these issues 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Around 82% of such hazards arise from tyre usage and processing, which eventually contributes to around 20% of total environmental hazardousness. 2 Recycling, reusing, and utilization of less hazardous/ renewable resource-based raw materials are the possible methods suggested by the experts to overcome these issues. 3 However, there is a limit to recycling and reusing of tyre products and ultimately all will end up as waste materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations